Antithrombotic management and outcomes of patients with atrial fibrillation treated with NOACs early at the time of market introduction: Main results from the PREFER in AF Prolongation Registry - Renda, Giulia; Pecen, Ladislav; Patti, Giuseppe; Ricci, Fabrizio; Kotecha, Dipak; Siller-Matula, Jolanta M; Schnabel, Renate B; Wachter, Rolf; Sellal, Jean-Marc; Rohla, Miklos; Lucerna, Markus; Huber, Kurt; et al. (Internal and emergency medicine, 2021)
The management of patients with atrial fibrillation (AF) has rapidly changed with increasing use of non-vitamin K antagonist oral anticoagulants (NOACs) and changes in the use of rhythm control therapy. The prevention of thromboembolic events European Registry in Atrial Fibrillation Prolongation Registry (PREFER Prolongation) enrolled consecutive patients with AF on NOACs between 2014 and 2016 in a multicentre, prospective, observational study with one-year follow-up, focusing on the time of introduction of NOACs. Overall, 3783 patients were enrolled, with follow-up information available in 3223 (85%). Mean age was 72.2 ± 9.4 years, 40% were women, mean CHA2DS2VASc score was 3.4 ± 1.6, and 2587 (88.6%) had a CHA2DS2VASc score ≥ 2. Rivaroxaban was used in half of patients, and dabigatran and apixaban were used in about a quarter of patients each; edoxaban was not available for use in Europe at the time. Major cardiovascular event rate was low: serious events occurred in 74 patients (84 events, 2%), including 24 strokes (1%), 62 major bleeds (2%), of which 30 were life-threatening (1%) and 3 intracranial (0.1%), and 28 acute coronary syndromes (1%). Mortality was 2%. Antiarrhythmic drugs were used in about 50% of patients, catheter ablation in 5%. Adverse events were low in this contemporary European cohort of unselected AF patients treated with NOACs already at the time of their first introduction, despite high thromboembolic risk.
Keywords: pyrazoly; Registries; Humans; dabigatran; Dabigatran; registrace; Pyridones; Female; Aged; Prospective Studies; senioři; lidé; Administration, Oral; Atrial Fibrillation; Europe; fibrilace síní; Major cardiac or cerebrovascular events; rivaroxaban; NOAC; Registry; ženské pohlaví; Male; pyridony; aplikace orální; Rivaroxaban; mužské pohlaví; prospektivní studie; Pyrazoles; Atrial fibrillation; Anticoagulants; Evropa; Bleeding; inhibitory faktoru Xa; Factor Xa Inhibitors